Evaluation of two levels of protein in diets for the Sabaleta Brycon Henni juveniles (Eigenmann, 1913). - Aguirre Gaviria, María Cristina; Muñoz Arroyave, Luz Elena (Revista Colombiana de Investigaciones Agroindustriales, 2015)
This experiment was conducted in order to evaluate two levels of protein in juvenile sabaleta, (Brycon henni) with two diets formulated semi-purified with 24% and 26% protein. 132 fishes were used obtained from the wild, with a weight of 1-3g, 3,1-5g, 5,1-7g, with 22 fish per channel (3 replicates). The animals were acclimated to the conditions of confinement of the fish station UNISARC fed with phytoplankton and zooplankton obtained from the ponds of the fish station for a month and then offered food, five times a day for 30 days. At the end of this period the animals were weighed and slaughtered for determining specific growth rate (SGR), survival, protein efficiency ratio (TEP), daily feed intake (CDA), feed conversion (FCA) condition factor (K), percent weight gain (GP), daily consumption of protein / fish (GPD), hepatosomatic index (IHS), fat (GM), viscerosomatic Index (IVS). The results were evaluated as a randomized block design, block taking the weight range with a normal weight curve, comprising 2 treatments, with 3 replications. Treatment with 24% protein showed better characteristics in weight gain day, GP, TEP and FCA. Food with 26% protein showed better values for properties SGR, K, IHS, IVS, CDA and DGP. Survival for both treatments was 100%. The experiment results indicated that no significant differences (p <0.05) occurred in any of the variables studied. Para citar este artículo Aguirre, M. y Muñoz, L. (2015). Evaluación de dos niveles de proteína en dietas para juveniles de Sabaleta Brycon Henni (Eigenmann, 1913). Rev. Colomb. Investig. Agroindustriales, 2(1), 61-68. DOI: https://doi.org/10.23850/24220582.170